PEMBUATAN DAN KARAKTERISASI KERTAS DARI DAUN NANAS DAN ECENG GONDOK - Vivien Ayunda (Saintia Fisika, 2013)
ABSTRACT Research on the manufacture and characterization of paper made from a mixture of pineapple leaf and water hyacinth has been done. The research was conducted using semi-chemical, aiming to obtain an alternative raw material for paper and find out the optimum composition of the mixture of pulp pineapple leaf and water hyacinth. Variations weight percent of the mixture is 100:0%, 80:20%, 60:40%, 40:60%, 20:80%, 0:100%. Pineapple lef and water hyacinth cooked using a 1,5% solution of NaOH, at a temperature of 100oC, then performed with Ca(ClO)2 bleaching process, dried, and then the pulp is mixed according to the composition of the mixture that has been designed. Best composition of a mixture of pineapple pulp and pulp leaves are water hyacinth leaf pineapple pulp 60% and 40% water hyacinth pulp in which the composition has a grammage 71,23 gr.m-2 and tear resistance 90,5874 mili N in accordance with standart SNI 14-01115-1998 for food wrapping paper with grammage value of 80 gr.m-2 and tear resistance 99 mili N. Keywords: Pineapple leaf, Water hyacinth, pulp, and paper.